Towards 2022: what are prevention and risk reduction in Alzheimer’s disease? (2021)
The increase in life expectancy has led in recent years to neurodegenerative pathologies, such as Alzheimer’s disease, that were strange in the last century, now become so frequent that there is talk of a new epidemic. It is estimated that approximately 50000000 patients suffer dementia around the world (World Health OrganizationWHO, 2012). Alzheimer’s disease is the most common dementia, and brain pathology begin up to 25 years before the first clinical symptoms appear (Bateman et al., 2012). Thus, Alzheimer currently has five stages, the pre-symptomatic, the mild cognitive impairment, and the mild, moderate and severe dementia. Since the original description in 1904 by Alois Alzheimer, the disease could only be definitively diagnosed by neuropathological, and the clinical diagnosis was only probable or possible (NINCDS ADRDA, McKhan et al., 1984). In recent years, more detailed knowledge of structural neuroimaging (hippocampal volume by MRI), metabolic (FDG-PET), molecular (amyloid PET), and cerebrospinal fluid studies (Aβ42, tau and f-tau) make it possible to diagnose Dementia due to Alzheimer’s disease while the patient is alive (McKhan et al., 2011) and even at pre-symptomatic stage of the disease (Sperling et al, 2011).